Metabolic Reprogramming and Longevity of Tissue-Resident Memory T Cells - Pan, Youdong; Kupper, Thomas S. (Frontiers in Immunology, 2018)
Tissue-resident memory T cells (TRM) persist in peripheral tissues for long periods of time in the absence of antigenic stimulation. Upon re-encounter with cognate antigen, TRM trigger an immediate immune response at the local tissue microenvironment and provide the first line of host defense. TRM have been reported to play significant roles in host anti-microbial infection, cancer immunotherapy and pathogenesis of a number of human autoimmune diseases, such as psoriasis, vitiligo and atopic dermatitis. TRM display a distinct gene transcriptome with unique gene expression profiles related to cellular metabolism that is different from naive T cells (TN), central memory T cells (TCM) and effector memory T cells (TEM). Skin CD8+ TRM up-regulate expression of genes associated with lipid uptake and metabolism, and utilize mitochondria fatty acid β-oxidation to support their long-term survival (longevity) and function. In this review, we will summarize the recent progresses in the metabolic programming of TRM, and will also discuss the potential to target the unique metabolic pathways of TRM to treat TRM-mediated diseases.